Fast and Accurate Prediction of Electromagnetic and Temperature Fields for SPMSM Equipped with Unequally Thick Magnetic Poles - Feng Liu; Xiuhe Wang; Lingling Sun; Hongye Wei (CES Transactions on Electrical Machines and Systems, 2025)
With the continuous upgrading of traditional manufacturing industries and the rapid rise of emerging technology fields, the performance requirements for the permanent magnet synchronous motors (PMSMs) have become higher and higher. The importance of fast and accurate electromagnetic thermal coupling analysis of such motors becomes more and more prominent. In view of this, the surface-mounted PMSM (SPMSM) equipped with unequally thick magnetic poles is taken as the main object and its electromagnetic thermal coupling analytical model (ETcAM) is investigated. First, the electromagnetic analytical model (EAM) is studied based on the modified subdomain method. It realizes the fast calculation of key electromagnetic characteristics. Subsequently, the 3D thermal analytical model (TAM) is developed by combining the EAM, the lumped parameter thermal network method (LPTNM), and the partial differential equation of heat flux. It realizes the fast calculation of key thermal characteristics in 3D space. Further, the information transfer channel between EAM and TAM is built with reference to the intrinsic connection between electromagnetic field and temperature field. Thereby, the novel ETcAM is proposed to realize the fast and accurate prediction of electromagnetic and temperature fields. Besides, ETcAM has a lot to commend it. One is that it well accounts for the complex structure, saturation, and heat exchange behavior. Second, it saves a lot of computer resources. It offers boundless possibilities for initial design, scheme evaluation, and optimization of motors. Finally, the validity, accuracy, and practicality of this study are verified by simulation and experiment.